What has happened to teacher assessment of science in English primary schools? Revisiting evidence from the Primary Science Quality Mark. Issue 1 (2nd January 2023) - Earle, Sarah; Turner, Jane
ABSTRACT: Background: An earlier article in this journal provided a mapping of primary science teacher assessment practices in England using teacher reflections written for Round 4 of the Primary Science Quality Mark (PSQM). Purpose: In the intervening years, the National Curriculum and statutory assessment system of levels has been replaced with a system of age-related expectations and a call for schools to develop their own systems of assessment. The aim of this study is to find out whether schools have changed their practices and to consider the ongoing changes they are making to their systems of assessment. Sample: The previous analysis of 91 Round 4 schools in March 2013 was compared to teacher reflections from 200 schools from across England in the more recent PSQM Round 13, June 2017. Design and methods: Qualitative content analysis was used to code the reported assessment methods in PSQM Round 13. The frequency of assessment methods were compared to the Round 4 mapping. Results: Reported practice in summative assessment in Round 13 included more 'ongoing' assessment information, which could potentially support a more valid sampling of the construct, but there was a lack of clarity regarding the use of data tracking systems. In the PSQM year, subject leaders described starting or developing the use of a range of published and school developed resources to support assessment practices in formative and summative assessment. Conclusion: Changing statutory assessment processes instigates change in school practices, but without support for teacher assessment literacy, the implementation of new assessment systems may not lead to clear processes for assessment which support learning in primary science.